Mobile Learning dalam Pendidikan: Analisis Bibliometrik - Dewantara, Kadek Teguh Wahyu (Upgrade : Jurnal Pendidikan Teknologi Informasi, 2024)
Mobile Learning is a learning method that utilizes mobile devices such as smartphones, tablets and laptops to access educational materials and carry out learning activities. The aim of this research is to present bibliometrics and bibliographies of various literature on Mobile Learning in education. Bibliometric analysis using VOSviewer contained 993 pieces of literature from the Google Scholar database published from 2022-2024. The research results show a decline from year to year. In 2022 there will be a decline due to only a few articles being published. There are 6 clusters. Cluster 1 (18 items), cluster 2 (14 items), cluster 3 (14 items), cluster 4 (10 items), cluster 5 (9 items), cluster 6 (5 items). In addition, journals are published by mostly Indonesian researchers. This study can help educators, researchers, and policy makers to understand the latest developments in this field and make informed decisions regarding the use of m-learning in learning.